Violence, Language and Fascism: Reproductions of Discursive Identities - Favell, Andrew M (PINS-Psychology in Society, 2026)
Violence is explored as a language mode by which one attempts to bring oneself forth in a world of transient meanings and uncertainty. Violence is problematised, not as a deviation from a norm of ordered identities, but rather as the norm of such identification itself carried to extremes. In this light, violence is posited as serving particular maintenance functions by means of which a fragile identification is sustained through the over-encoding of the differences expressed by the Other.